Dispersed limitation and homogeneous selection drive the eukaryotic microbial community assembly and network stability in the coastal China sea - Chen, Zhuo; Gu, Ting; Sun, Jun (Frontiers in Marine Science, 2024)
Eukaryotic microorganisms were the key components of marine microecosystems and were involved in biogeochemical cycling processes. Although oceanographers have emphasized their importance in open oceans, the current understanding was not comprehensive enough about the assembly processes and co-occurrence network of different fraction eukaryotic microbial communities in the coastal China sea. We used co–occurrence networks and ecological process model to investigate possible ecological interactions in two fractions (small fraction 0.22–3 μm; large fraction 3–200 μm) of eukaryotes throughout different depths and geographical regions of coastal China sea. We found that environmental distance shapes the diversity of the two fractions eukaryotic microorganisms. Dispersal limitation and homogeneous selection processes were the key drivers of eukaryotic microbial community assembly. Co-occurrence network analysis showed that the networks of the 0.2–3 μm eukaryotes more nodes and edges, with more complex interactions between microorganisms, and higher network stability than that of 3–200 μm eukaryotic microorganisms. Temperature, oxygen, salinity, and nutrients play the crucial role in the abundance of two fractions eukaryotic microorganisms. These results crystallize the knowledge of eukaryotic microbes in the coastal China sea, which was essential for addressing the challenges posed by global change.